Mitotic gene regulation by the N-MYC-WDR5-PDPK1 nexus - Sarah A. Streeter; Alexandria G. Williams; James R. Evans; Jing Wang; Alissa D. Guarnaccia; Andrea C. Florian; Rafet Al-Tobasei; Qi Liu; William P. Tansey; April M. Weissmiller (BMC Genomics, 2024)
Abstract Background During mitosis the cell depends on proper attachment and segregation of replicated chromosomes to generate two identical progeny. In cancers defined by overexpression or dysregulation of the MYC oncogene this process becomes impaired, leading to genomic instability and tumor evolution. Recently it was discovered that the chromatin regulator WDR5—a critical MYC cofactor—regulates expression of genes needed in mitosis through a direct interaction with the master kinase PDPK1. However, whether PDPK1 and WDR5 contribute to similar mitotic gene regulation in MYC-overexpressing cancers remains unclear. Therefore, to characterize the influence of WDR5 and PDPK1 on mitotic gene expression in cells with high MYC levels, we performed a comparative transcriptomic analysis in neuroblastoma cell lines defined by MYCN-amplification, which results in high cellular levels of the N-MYC protein. Results Using RNA-seq analysis, we identify the genes regulated by N-MYC and PDPK1 in multiple engineered CHP-134 neuroblastoma cell lines and compare them to previously published gene expression data collected in CHP-134 cells following inhibition of WDR5. We find that as expected N-MYC regulates a multitude of genes, including those related to mitosis, but that PDPK1 regulates specific sets of genes involved in development, signaling, and mitosis. Analysis of N-MYC- and PDPK1-regulated genes reveals a small group of commonly controlled genes associated with spindle pole formation and chromosome segregation, which overlap with genes that are also regulated by WDR5. We also find that N-MYC physically interacts with PDPK1 through the WDR5-PDPK1 interaction suggesting regulation of mitotic gene expression may be achieved through a N-MYC-WDR5-PDPK1 nexus. Conclusions Overall, we identify a small group of genes highly enriched within functional gene categories related to mitotic processes that are commonly regulated by N-MYC, WDR5, and PDPK1 and suggest that a tripartite interaction between the three regulators may be responsible for setting the level of mitotic gene regulation in N-MYC amplified cell lines. This study provides a foundation for future studies to determine the exact mechanism by which N-MYC, WDR5, and PDPK1 converge on cell cycle related processes.